2009
DOI: 10.1371/journal.pone.0006606
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination of Factors, Termed SPIE, which Promotes Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells

Abstract: BackgroundStromal-Derived Inducing Activity (SDIA) is one of the most efficient methods of generating dopaminergic (DA) neurons from embryonic stem cells (ESC). DA neuron induction can be achieved by co-culturing ESC with the mouse stromal cell lines PA6 or MS5. The molecular nature of this effect, which has been termed “SDIA” is so far unknown. Recently, we found that factors secreted by PA6 cells provided lineage-specific instructions to induce DA differentiation of human ESC (hESC).Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 67 publications
6
72
0
2
Order By: Relevance
“…Several prior studies have analyzed factors secreted from PA6 stromal cells and have suggested those that might be effective at inducing or maintaining dopamine neurons from ESCs. Vazin et al (2009) performed genome expression analysis by comparing PA6 cells with other cell lines and concluded that four factors were mainly responsible for PA6 cell-derived effects on ESCs: stromal cell-derived factor 1 (SDF-1/CXCL12), pleiotrophin (PTN), insulin-like growth factor 2 (IGF2), and ephrin B1 (EFNB1). They used a combination of these four factors to induce differentiation of TH-positive neurons successfully from human ESCs (Vazin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior studies have analyzed factors secreted from PA6 stromal cells and have suggested those that might be effective at inducing or maintaining dopamine neurons from ESCs. Vazin et al (2009) performed genome expression analysis by comparing PA6 cells with other cell lines and concluded that four factors were mainly responsible for PA6 cell-derived effects on ESCs: stromal cell-derived factor 1 (SDF-1/CXCL12), pleiotrophin (PTN), insulin-like growth factor 2 (IGF2), and ephrin B1 (EFNB1). They used a combination of these four factors to induce differentiation of TH-positive neurons successfully from human ESCs (Vazin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Vazin et al (2009) performed genome expression analysis by comparing PA6 cells with other cell lines and concluded that four factors were mainly responsible for PA6 cell-derived effects on ESCs: stromal cell-derived factor 1 (SDF-1/CXCL12), pleiotrophin (PTN), insulin-like growth factor 2 (IGF2), and ephrin B1 (EFNB1). They used a combination of these four factors to induce differentiation of TH-positive neurons successfully from human ESCs (Vazin et al, 2009). Wnt5a is also important for the development of DA neurons (Parish et al, 2008) and is expressed by PA6 cells (Hayashi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The multivalent binding of a ligand (simultaneous binding to one assembly of receptors) has recently been shown to drive receptor clustering at the nanoscale level (Conway et al, 2013). Super-resolution microscopy has been used to visualize ephrin-B2-driven clustering of the EphB4 receptor at the nanoscale level on adult neuronal stem cells, as ephrin-B-EphB signaling has been shown to regulate neuronal stem cell differentiation (Ashton et al, 2012;Conway et al, 2013;Vazin et al, 2009). The multivalency of a recombinant ephrin-B2 ectodomain conjugated to a soluble biopolymer strongly enhanced the bioactivity of ligands, resulting in the induction of neuronal stem cell signaling -i.e.…”
Section: Initial Events Upon Ligand Binding -Recruitment Assembly Anmentioning
confidence: 99%
“…An Lmx1a promoter was used in hESCs to promote differentiation of 10 to 20% TH+ neurons (Friling et al, 2009). Efforts to improve the derivation of dopaminergic neurons have included formation of spherical neural masses (SNMs) instead of EBs prior to differentiation (Cho et al, 2008, Vazin et al, 2009. Elucidating the factors expressed in and secreted by stromal cells used to differentiate dopaminergic neurons included microarray studies.…”
Section: Dopaminergic Differentiationmentioning
confidence: 99%
“…Additionally, receptors for these genes were more highly expressed in NSCs compared to hESCs. A study using various 398 combinations of factors which activated these receptors or replicated the factors expressed by PA6 cells determined that the combination of factors termed SPIE (SDF-1, PTN, IGF2, and EFNB1) was most effective at differentiating hESCs towards dopaminergic neurons (Cho et al, 2008, Vazin et al, 2009). However, a highly efficient and effective method of dopaminergic differentiation has not been obtained.…”
Section: Dopaminergic Differentiationmentioning
confidence: 99%